Esophageal carcinoma: Intravoxel incoherent motion diffusion‐weighted MRI parameters and histopathological correlations. Issue 1 (7th May 2018) - Zhu, Shaocheng; Wei, Yi; Gao, Feifei; Li, Linlin; Liu, Yuehua; Huang, Zixing; Tang, Hehan; Zheng, Dandan; Wei, Xiaocheng; Sun, Tingyi; Song, Bin
Abstract : Background: The pathological grade of esophageal carcinoma is highly determinant of patient prognosis, but it still cannot be adequately evaluated preoperatively. Compared with conventional diffusion‐weighted imaging (DWI), intravoxel incoherent motion (IVIM) diffusion‐weighted MRI can separate true molecular diffusion and perfusion in tissues and has been shown to be useful in characterizing malignant tumors. There is no report that compared IVIM and conventional DWI in grading esophageal carcinoma. Purpose: To prospectively determine the diagnostic performance of conventional DWI and IVIM models in differentiating the pathological differentiated grade of esophageal carcinoma. Study Type: Prospective. Population: A cohort comprising 81 patients with newly diagnosed esophageal squamous cell carcinoma (ESCC) between December 2015 and August 2017 were evaluated. Field Strength/Sequence: 3.0T, axial echo‐planer imaging, fast spin echo (FSE) sequence, IVIM sequence (b = 0, 20, 50, 80, 100, 150, 200, 400, 600, 800, 1000, 1200). Assessment: Apparent diffusion coefficient (ADC), true ADC (ADCslow ), pseudo ADC (ADCfast ), and perfusion fraction ( f ) of each tumor were calculated by two independent radiologists. Histopathologic grade was used as the reference standard. Statistical Tests: Games‐Howell test; diagnostic accuracy; Spearman correlation; intraclass correlation coefficient; and Bland–Altman analysis. Receiver operating characteristics (ROC) curves. Results: ADCslow demonstrated the highest area under curve (AUC) with a value of 0.830 (95% confidence interval [CI]: 0.730–0.904) and 0.816 (95% CI: 0.714–0.893) by two radiologists, followed by ADC with a value of 0.754 (95% CI: 0.646–0.843) and 0.761 (95% CI: 0.653–0.848). Good correlation was obtained between the histologic grade and ADCslow ( r (R1) = 0.748, r (R2) = 0.720) and ADC ( r (R1) = 0.576, r (R2) = 0.571). Data Conclusion: ADCslow and ADC had a significantly higher performance than the ADCfast and f, and ADCslow had a significantly higher performance than the ADC. Level of Evidence : 1 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2019;49:253–261.